Approaching electrical circuit understanding with circuit builder virtual laboratory - Santoso, Purwoko Haryadi; Munawanto, Nino (Jurnal Ilmiah Pendidikan Fisika Al-Biruni, 2020)
Nowadays, most students are familiar with the notebook for daily use. The compactness and flexibility of the notebook offer more benefits than a PC. The teachers can engage it during teaching physics. Hence, this research had developed an electrical circuit virtual experiment that acts like real experiments. It can be accessed easily by students in their notebook. This study introduces a flash-based animation Circuit Builder as a simulation designed to help students understand the electrical circuit. This study's purposes were: (1) to analyze the feasibility level of Circuit Builder for enhancing students’ electrical circuit mastery and (2) to know the effectiveness of Circuit Builder based on students’ electrical circuit mastery. Circuit Builder was developed by 4D (Define, Design, Develop, and Disseminate) model. The feasibility level was analyzed by CVI (Content Validity Index). Then, the effectiveness was tested with effect size. This study proved that the virtual laboratory "Circuit Builder” was feasible in physics class with a moderate effect size. The virtual laboratory could improve students’ electrical circuit mastery than doing practices with traditional laboratories.